The Aspect of Students' Speaking Anxiety in Using IGTV (RETAIN, 2020)
Speaking anxiety has been very difficult to overcome in English teaching and learning process for 3 decades. Every student has their own speaking anxiety with various rates and the teacher needs the answer to solve this problem by considering the anxiety-speaking component of the students. Students in some situations have trouble with speaking anxiety and trouble speaking work. Therefore, they need a creative media or resources that can help to reduce their anxiety in speaking and make learning more exciting and engaging. In this study IGTV as a tool to identify the aspect of students’speaking anxiety. The researcher tends to investigate the use of IGTV and find the aspect speaking anxiety that student have.This study used Quantitative design to investigate the aspect speaking anxiety of IGTV as a tool for students. Furthermore, the data were obtained through giving questionnaires and using survey method. The participants of this study were taken from one of senior high school students in East Java. The results showed a positive influence as the students have the cognitive aspect of speaking anxiety when they used IGTV.